Introduction and Development Of Typical Barru Food As A Potential For Culinary Tourism - Hartati Hartati; Maslan Maslan; Yunita Yunita (Universitas Muhammadiyah Enrekang, 2024)
The introduction and development of Barru specialty food as a culinary tourism potential is a strategic step in increasing tourist attraction in this area. Barru, located on the west coast of South Sulawesi, has a culinary richness rooted in Bugis cultural traditions, with various typical dishes such as Pallu Basa, Coto Barru, and Barobbo. These foods have rich flavors and spices, reflecting the rich culture and history of the Barru people. Barru's culinary tourism potential needs to be developed as a superior tourist attraction that can increase tourist visits and support the local economy. This article aims to explore Barru's culinary potential in the context of tourism development, by emphasizing the importance of promoting, managing and improving culinary facilities that can support the tourist experience. The development of culinary tourism in Barru does not only depend on the quality of food, but also on the sustainability of traditions and the involvement of local communities in the culinary production and presentation process. Therefore, this article offers recommendations regarding organizing culinary festivals, using social media as a promotional tool, and improving culinary tourism infrastructure to attract tourists. With an integrated approach, Barru culinary tourism is expected to become one of the main pillars in regional tourism development, as well as providing a positive impact on the local economy and cultural preservation.